D’infimes différences. Pratique et circulation des jeux de ficelle chez les femmes du Chaco paraguayen - David Jabin (Journal de la Société des Américanistes)
Since the beginning of the 20th century, a major effort has been made to develop a method of recording and comparing the numerous string games practiced in various parts of the world. Originally, within the framework of the diffusionist paradigm, the aim was to look for similarities, as clues to technical borrowings that could help to understand contacts between human groups. Based on fieldwork carried out in the central Paraguayan Chaco, where indigenous people live in agricultural settlements established by the Mennonites to implement intensive agriculture, the author compares the string figure making of Nivacle and Enlhet women in two neighboring communities. The aim is to understand the meaning of the technical and graphic differences observed in these two communities, and then, in contrast to the diffusionist hypothesis, to examine the way in which string figure making, like language or handicrafts, participates in the processes of ethnic affiliation.